Impact of Almond Variety on “Amaretti” Cookies as Assessed through Image Features Modeling, Physical Chemical Measures and Sensory Analyses - Marco Campus; Manuela Sanna; Giandomenico Scanu; Riccardo Di Salvo; Luciano De Pau; Daniela Satta; Antonio Demarcus; Tonina Roggio (Foods, 2020)
In the present study, the influence of almond variety on color, chemical, physical and sensory characteristics of “amaretti” cookies during the shelf life, was assessed. Four varieties were chosen for the study, two of which were local (Cossu, Arrubia) and two widely cultivated (Tuono, Texas). Almonds have been characterized in the content of proteins, crude fat, amygdalin and fatty acids profile. The evolution of the characteristics during the shelf life hasbeen measured through image data modeling, texture, physical chemical and sensory analyses. Data were then treated with a multivariate approach performing a PCA. Image analysis and fitting on log normal and powerlaw functions highlighted the influence of the variety on the total area affected by surface breakages, and on the distribution of the cracking surfaces dimension classes. Texture parameters (crust hardness, thickness and work of deformation) were negatively correlated to moisture content. Sensory profile confirmed the differences in tactile features measured through instrumental texture, while slight to no differences were found in odor profile. Consumer test showed an higher acceptability for Arrubia, Texas and Tuono samples throughout the shelf life, while Cossu samples were less accepted. Overall, the choice of almond variety influences product features and liking of almond products, therefore it represents an important phase to direct the choice of both farmers and confectionery manufacturers.